Conscious and Unconscious State of Dreams in Girish Karnad’s The Dreams of Tipu Sultan - Kamalakkannan, K.; Geethapriya, E. (International Journal of Psychosocial Rehabilitation, 2020)
Girish karnad's in his play The Dreams of Tipu Sultan utilize the idea of dreams to demonstrate the defeat of Tipu Sultan through his fantasies. The fantasies of Tipu Sultan can be deciphered as image or a sign which centers around his destruction later on. The fantasies book (Khwab-nama) was plundered from Seringapatam alongside different books. The book was not in library or the regal library in Seringapatam. It was found covered up in the bed office of Tipu King royal residence Lal Mahal the destruction of which can be seen today before the Sri Ranganatha Swamy Temple. Tipu ruler, one of the most politically discerning and shocking figures in present day Indian history. In the play he had four dreams however in history has 37 dreams.